Business intelligence para gestão dos dados pessoais do corpo docente do ilaach/unila - Cruz, Andréia da (2023)
In recent decades, in the face of digital transformations occurring in society, the use of technologies to manipulate data has stood out in the management of corporate informational assets. Driven by the need to address issues such as security and compliance, organizations use Business Intelligence (BI) resources to ensure their sustainability. In this context, based on ethical principles of Data Governance (DG), the present study proposes the development of a BI solution using data from the faculty of the Latin American Institute of Art, Culture, and History – ILAACH at the Federal University of Latin American Integration (UNILA). The methodology used to achieve this objective encompasses a qualitative, descriptive, and exploratory approach to action research (AR), whose phases are consistent with the steps of the CRISP-DM data mining model. Among the listed data collection instruments are literature and documentary research, participant observation, questionnaire application, and focus group (FG). The analysis of the collected content was carried out through categorization. The research results demonstrated that the use of intelligent data management tools facilitates the visualization of crucial information for ILAACH managers and the technical team. However, quality issues were identified in certain data, limiting users' ability to obtain insights and reducing the amount of material suitable for use in constructing informative panels. Nevertheless, the tool proved to be reliable and useful in addressing the demands related to the faculty of the Institute. In this regard, Business Intelligence (BI) documents - inventory and data dictionary (DD) - have become important allies in achieving this investigation. Developed under the premises of the General Data Protection Law - LGPD, these elements allowed the understanding of data from its life cycle, considering metadata. In conclusion, it was found that the use of tools providing intelligent management of information assets can effectively contribute to optimizing the administrative routine and facilitating the decisionmaking process of the studied organization. The contributions of this work encompass the enrichment and consolidation of academic and scientific literature, the implementation of theoretically overlooked precepts institutionally, as well as the promotion of improvements and greater efficiency in public management.